Comparison of MPPT Technique of Photovoltaic Systems For Interleaved Soft Switching Boost Converter (Asian Journal of Current Engineering and Maths, 2016)
Renewable energy especially solar photovoltaic is seen as an important alternative source of energy for the future. In order to improve the energy efficiency, it is important for the PV system to operate at its maximum power point. Maximum power varies with solar radiation and solar cell temperature. The need of MPPT is that under different atmospheric conditions, the array operating voltage should move close to the maximum power. In this project, Interleaved Boost Converter (IBC) is used for PV applications, which comprises of two boost converters operating 1800 out of phase. By splitting the current into two power paths, conduction (I2R) losses can be reduced thus increasing overall efficiency compared to a single-phase converter. As the two phases are combined at the output capacitor, effective ripple frequency is doubled, which in turn reduces the ripple voltage. Hence this topology reduces input current ripple, output voltage ripple and size of the components. The switching losses can be reduced by adopting a zero voltage soft-switching method. Fuzzy logic controller (FLC) is used which is an MPPT algorithm. The values for this controller are obtained by using another MPPT algorithm called Perturb and Observe (P&O) technique. The complexity of search algorithm is reduced by fuzzy logic. The fuzzy Controller tracks the MPP accurately. Hence the FLC is preferred